Novelty Designed Hybrid Organic-Inorganic Nanocomposites from Functional Palm Oil - Suryani, Suryani (Jurnal Sains dan Teknologi Reaksi, 2008)
Polyurethanes (PUs) are very versatile polymeric materials with a wide range of physical and chemical properties. PUs also have desirable properties such as high abrasion resistance, tear strength, shock absorption, flexibility and elasticity. Although they have poor thermal stability that however can be improved by using treated clay. The objective of the present work is to study the thermal stability of polyurethane, polyurethane/montmorillonite (PU CTAB-mont 3% wt) and polyurethane/montmorillonite that contain moca nanocomposites are based on palm oil polyol. The interest of investigating the synthesis of polyurethane/clay nanocomposites based on palm oil polyol is to explore the use of palm oil polyol to replace petrochemical based polyol partially. Polyurethane/clay nanocomposites were prepared by a pre-polymer method and were evaluated by fourier transform infrared spectra (FTIR) to determine micro-domain structures of segmented PU, PU CTAB-mont 3% wt, and PU Moca CTAB-mont 3% wt. The morphology of the nanocomposites were characterized by X-ray diffraction (X-RD) and flame retardant was investigated with thermogravimetric analysis (TGA). The result showed that adding clay and moca demonstrated better thermal stability in comparison with the virgin polyurethane.Keywords : Nanocomposite, polyurethane, synthesis, palm oil polyol